KRITIK HUKUM ISLAM TERHADAP UNDANG-UNDANG NO. 42 TAHUN 2008 TENTANG PEMILIHAN PRESIDEN DAN WAKIL PRESIDEN DI INDONESIA - Sutisna Sutisna (Sekolah Tinggi Agama Islam Al Hidayah Bogor, 2017)
According to Imam Al-Mawardi, Caliph, King, Sulthan, the Imamate or the head ofstate to replace prophetic institution in order to protect and regulate the religious life of the world. Al-Mawardi has set clear requirements for a head of state. Indonesia, which is one of the countries in the world with a majority Muslim population and the largest number in the world, heads of State and lifting mechanisms thought to follow the requirements of Islamic law. The results showed that the election of the head of state in Islam is done in ways that vary according to the circumstances. These differences can be understood as the dynamics of the election of Heads of State in Islam which will continue to take place according to the roll of time, circumstances, and conditions. Election of the president and vice president in Indonesia has undergone significant changes. In the Old Order and the New Order president and vice presidential election conducted by members of the Assembly. Meanwhile, since the Reform Era to the present election of president and vice president made directly by the people. Electoral system and the president and vice president of the terms of the president and vice president candidates in Indonesia as described in Law No. 42 of 2008 on the General Election of President and Vice President are in accordance with Islamic law. In fact, according to the author terms the president and vice president candidates contained in Law No. 42 of2008 was not only appropriate, but the adoption of Islamic law derived from the Quran and Al-Sunnah. Keyword: Criticism, the selection mechanism, terms, heads of state, Islamic law, Act